2021
DOI: 10.1186/s12984-021-00842-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of powered prostheses on user perspectives, metabolics, and activity: a randomized crossover trial

Abstract: Background Powered prosthetic ankles provide battery-powered mechanical push-off, with the aim of reducing the metabolic demands of walking for people with transtibial amputations. The efficacy of powered ankles has been shown in active, high functioning individuals with transtibial amputation, but is less clear in other populations. Additionally, it is unclear how use of a powered prosthesis influences everyday physical activity and mobility. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 31 publications
(20 reference statements)
1
42
0
Order By: Relevance
“…The present pragmatic, exploratory study aimed at determining whether anecdotal reports of individuals with TTA on reduced musculoskeletal pain when using a PwrAF reflect a common experience among users or just isolated occurrences. As the identification of subjects who are likely to benefit from a PwrAF has been a clinical challenge (9)(10)(11), it was decided to survey a bigger sample of individuals who had been fitted such foot in the past to obtain real-world, long-term use experiences with the PwrAF and passive prosthetic feet. Though recall of ratings for previous interventions has limitations and challenges, this pragmatic approach is very similar to clinical practice where patients are usually asked to compare their current symptoms to those they recall for time points in the past.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present pragmatic, exploratory study aimed at determining whether anecdotal reports of individuals with TTA on reduced musculoskeletal pain when using a PwrAF reflect a common experience among users or just isolated occurrences. As the identification of subjects who are likely to benefit from a PwrAF has been a clinical challenge (9)(10)(11), it was decided to survey a bigger sample of individuals who had been fitted such foot in the past to obtain real-world, long-term use experiences with the PwrAF and passive prosthetic feet. Though recall of ratings for previous interventions has limitations and challenges, this pragmatic approach is very similar to clinical practice where patients are usually asked to compare their current symptoms to those they recall for time points in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a commercially available powered prosthetic ankle-foot component (PwrAF) generates speeddependent push-off power that may be comparable with that of the natural ankle (6)(7)(8). However, the results on its impact on function, such as self-selected walking speed (7,(9)(10)(11)(12)(13), metabolic energy expenditure on level ground (7,(9)(10)(11) and inclines (8,10), patient-reported prosthetic function (12), and other aspects of prosthetic mobility have been inconclusive or conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe a significant effect of prosthetic ankle stiffness on metabolic expenditure, even when we normalized stiffness by each subject's preference. While it is known that metabolic cost is not highly sensitive to prosthesis mechanics during level walking [41,[60][61][62][63][64][65][66], these previous studies have assessed metabolic cost either as a function of weight-normalized prosthetic joint stiffness, or of categorical stiffness [64]. Given that we have consistently shown that there is no clear linear relationship between weight and preferred stiffness, it is possible that weight-normalization may have obscured any underlying effects, by not adequately aligning the minima of individual subjects' energy landscapes [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preference is inherently specific to the population from which it is measured, which increases its applicability as an efficacy criterion across pathologies, and drives device development toward solutions that meet patient needs. In light of these benefits, preference has emerged in the research setting as a potential indicator of device efficacy [39][40][41], and has recently been used in combination with humanin-the-loop optimization to tune the behavior of complex wearable mechatronic systems [42,43].…”
Section: Introductionmentioning
confidence: 99%